The dual PI3K/mTOR inhibitor BEZ235 restricts the growth of lung cancer tumors regardless of EGFR status, as a potent accompanist in combined therapeutic regimens - Wu, Yi-Ying (J Exp Clin Cancer Res, 2019)
BACKGROUND: Lung cancer is the most common cause of cancer-related mortality worldwide despite diagnostic improvements and the development of targeted therapies, notably including epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs). The phosphoinositide 3-kinase (PI3K)/AKT/mechanistic target of rapamycin (mTOR) signaling has been shown to contribute to tumorigenesis, tumor progression, and resistance to therapy in most human cancer types, including lung cancer. Here, we explored the therapeutic effects of co-inhibition of PI3K and mTOR in non-small-cell lung cancer (NSCLC) cells with different EGFR status. METHODS: The antiproliferative activity of a dual PI3K/mTOR inhibitor BEZ235 was examined by the WST-1 assay and the soft agar colony-formation assay in 2 normal cell lines and 12 NSCLC cell lines: 6 expressing wild-type EGFR and 6 expressing EGFR with activating mutations, including exon 19 deletions, and L858R and T790 M point mutations. The combination indexes of BEZ235 with cisplatin or an EGFR-TKI, BIBW2992 (afatinib), were calculated. The mechanisms triggered by BEZ235 were explored by western blotting analysis. The anti-tumor effect of BEZ235 alone or combined with cisplatin or BIBW2992 were also studied in vivo. RESULTS: BEZ235 suppressed tumor growth in vitro and in vivo by inducing cell-cycle arrest at G1 phase, but without causing cell death. It also reduced the expression of cyclin D1/D3 by regulating both its transcription and protein stability. Moreover, BEZ235 synergistically enhanced cisplatin-induced apoptosis in NSCLC cells by enhancing or prolonging DNA damage and BIBW2992-induced apoptosis in EGFR-TKI–resistant NSCLC cells containing a second TKI-resistant EGFR mutant. CONCLUSIONS: The dual PI3K/mTOR inhibition by BEZ235 is an effective antitumor strategy for enhancing the efficacy of chemotherapy or targeted therapy, even as a monotherapy, to restrict tumor growth in lung cancer treatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13046-019-1282-0) contains supplementary material, which is available to authorized users.